PERENCANAAN POLDER DAMANHURI (SEMANI) SEBAGAI ALTERNATIF PENGENDALI BANJIR PADA RUAS JALAN SENTOSA – REMAJA – A. YANI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - INDRAWAN, BUDI (KURVA S JURNAL MAHASISWA, 2013)
East Kalimantan Samarinda , has experienced rapid development , resulting in changes in Land use , particularly Watershed Damanhuri which currently has many crowded settlements , both in the upstream and downstream watershed . This resulted in a loss caused by the floods and reduced catchment area or water catchment and drainage systems that do not support the discharge capacity of the flowing water . Considering this, the anticipation of the widespread impact of flooding in the city of Samarinda , the author will plan as an alternative polder flood control in watershed Damanhuri . As a polder in the watershed planning Samarinda Damanhuri the design flood discharge based on the calculation time and the 25-year anniversary by using a pump with a capacity of 9 m3/sec obtained polder dimensions of length 400m and 250m width = 100,000 m2 ( A ) , with a depth of 3m , then the capacity the maximum flood that can be accommodated is 300,000 m3 .